Penerapan 5 Aspek Kunci Untuk Memenuhi Standart E-Fullfilment Pada Perusahaan: Studi Kasus Online Store Akai Print Perbaungan - Hafizh Wahyu Wijaya Marpaung; Afrillia Afrillia; Aprillina Putri; Cut Dila Sari ; Nurbaiti Nurbaiti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This scientific article discusses the implementation of 5 key aspects to meet e-fullfillment standards in a company. Consumer Management, Catalog Management, Order Management, Delivery Management, and Inventory Management. These five things are key processes to meet the "e-fulfillment" standard, which starts from ordering the product until the product is received by the consumer. This article aims to examine the theoretical basis, research methods, and findings related to the application of these five aspects in the printing company, namely Akai Print, which is also the case study object of this article. In this article, the type of research method used is qualitative, using an inductive approach. The unit of analysis in this research is the Akai Print printing company, where the data sources in this research are documents and direct information. The data collection technique used in this research is direct observation and literature study, then the method used is descriptive analysis. The results of our research found that these 5 key aspects really are the most important aspects in a company, especially companies that are oriented towards customer satisfaction, such as the printing company Akai Print. Then from that, Akai Print has also fully implemented these five key aspects in its business so that the e-fullfillment standard is achieved and can improve the quality of the company.